Penerapan Metode Activity Based Management dalam Meningkatkan Efisiensi Aktivitas dan Biaya Produksi pada PT Sinar Pure Foods International Bitung: Application Of Activity Based Management Method In Improving The Efficiency Of Activities And Production Costs At PT Sinar Pure Foods International Bitung - Pandey, Meyta (Jurnal LPPM Bidang EkoSosBudKum (Ekonomi,Sosial,Budaya, dan Hukum), 2024)
In this era, the growth in the business world is growing as is the technological advance, competition between companies is increasingly competitive. Pt puree foods international bitung is a manufacturing company with the production of tuna, and it has a long production process that allows for more illicit activities. This activity based management can measure the effectiveness of the process and identify how processes and activities can be improved to lower costs. The objective of the study is to promote the efficiency of activity and production costs of pure foods international bitung. The study USES a qualitative approach by taking a descriptive analysis. Studies have shown that there is a value-added activity of charging the fish in the can by hand, which should be done automatically in order to be processed into cutting so that time is more effective can be performed on an oxidation that can lower costs and achieve efficiency. Keywords: Activity Based Management, Cost Of Production, Activities